Campaigning as a Spitzenkandidat: are lead candidates aligned with their party's manifesto? - Valkova, Simona Hristova (2020)
Nowadays, political actors use Twitter as one of the main online tools to campaign and connect to their constituencies, and so do "Spitzenkandidaten". The "Spitzenkandidat" process, which was initially implemented in 2014, is a widely researched topic. However, with campaign personalization, being one of its main drivers, it is surprising to see the lack of literature on the subject specifically connected to the lead candidates in the Twitter sphere. This study is filling the gap in the academic literature by answering the question: "To what extent the 2019 Spitzenkandidaten represented their party's manifestos via their tweets or develop individualized campaigns?". The results reveal that the 2019 "Spitzenkandidaten" do not focus on personalization as a main tool in their Twitter behavior. Furthermore, the study shows how factors like the age of the candidate, their party orientation and whether candidates tweet or retweet more, is influencing the outcome.